2020
DOI: 10.1002/ejic.202000634
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Dynamics and Thermodynamic Properties of Bulk Phases and Monolayers of GaTe and InTe: A Comparison from First‐Principles Calculations

Abstract: The hybrid density functional theory was used to study the structural, vibrational, and thermodynamic properties of stable and hypothetical bulk GaTe and InTe polymorphs, as well as their monolayer counterparts. Criteria based on the vibrational frequencies have been proposed to distinguish between different monolayer structures. Heat capacity, entropy, and Helmholtz free energy have been calculated by summing the vibrational contributions over the corresponding Brillouin zone. The relative stability of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…The phase transformation between H phase and M phase in the gallium monochalcogenides suggests that surface formation energy (total energy) may be a key factor in the determination of the structural phases in the layered GaTe 1−x Se x (0 ≤ x ≤ 1) series. Some theoretical and experimental works have been conducted to evaluate the stable phase and formation conditions of H-GaTe and M-GaTe 32,34,42 and the most important issues are closely related to the synthesis temperature and layer thickness of the gallium telluride.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The phase transformation between H phase and M phase in the gallium monochalcogenides suggests that surface formation energy (total energy) may be a key factor in the determination of the structural phases in the layered GaTe 1−x Se x (0 ≤ x ≤ 1) series. Some theoretical and experimental works have been conducted to evaluate the stable phase and formation conditions of H-GaTe and M-GaTe 32,34,42 and the most important issues are closely related to the synthesis temperature and layer thickness of the gallium telluride.…”
Section: Resultsmentioning
confidence: 99%
“…For growth temperature, the synthesized GaTe will be H phase if the deposition temperature of the physical vapor deposition is lower than 600 °C, whereas the deposited film will be M phase if the growth temperature is larger than 700 °C42 . Previous densityfunctional theory (DFT) calculations revealed that the increase of temperature favors the formation of the monolayer form of GaTe by deposition and the total energy of the H-phase monolayer is lower than that of the M-phase monolayer, which presents a more stable hexagonal-phase form for the single-layer condition 34 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our calculations have been performed in the framework of periodic DFT using the hybrid exchange‐correlation functional M06 designed to describe thermochemistry and noncovalent interactions involving main‐group elements. [ 15 ] As shown by Bandura et al, [ 16 ] the M06 functional can reproduce the correct stability of the observed tetragonal InTe phase. Bloch sums of localized atomic orbitals implemented in the CRYSTAL17 computer code were used to expand the crystal orbitals.…”
Section: Computational Detailsmentioning
confidence: 81%
“…The number and position of the active modes resemble the configuration calculated in refs. 40,41 for h-GaTe with thicknesses between ML and bulk. Following this comparison, the modes are named as A 1…”
Section: Results and Discussion Epitaxial Layered Hexagonal Gate On S...mentioning
confidence: 99%